2015
DOI: 10.1097/qai.0000000000000809
|View full text |Cite
|
Sign up to set email alerts
|

Using Molecular HIV Surveillance Data to Understand Transmission Between Subpopulations in the United States

Abstract: Background Studying HIV transmission networks provides insight into the spread of HIV and opportunities for intervention. We identified transmission dynamics among risk groups and racial/ethnic groups in the United States. Methods For HIV-1 pol sequences reported to the U.S. National HIV Surveillance System during 2001–2012, we calculated pairwise genetic distance, identified linked pairs of sequences (those with distance ≤1.5%), and examined transmission category and race/ethnicity of these potential transm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
139
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 138 publications
(151 citation statements)
references
References 23 publications
12
139
0
Order By: Relevance
“…[28][29][30][31] Transmission clusters can provide insight into shifts in social and structural dynamics influencing transmission over time and the role of social distance and other structural influences on transmission, independent of participant-reported history. 32 There is great potential for using these data to help identify segments of the population at highest risk for incident HIV infection, which can inform the mechanisms, upper limits of reach, and targeting for network-based HIV testing and care interventions, PrEP, and other social and behavioral intervention.…”
Section: Identifying Transmission Clustersmentioning
confidence: 99%
“…[28][29][30][31] Transmission clusters can provide insight into shifts in social and structural dynamics influencing transmission over time and the role of social distance and other structural influences on transmission, independent of participant-reported history. 32 There is great potential for using these data to help identify segments of the population at highest risk for incident HIV infection, which can inform the mechanisms, upper limits of reach, and targeting for network-based HIV testing and care interventions, PrEP, and other social and behavioral intervention.…”
Section: Identifying Transmission Clustersmentioning
confidence: 99%
“…A similar pattern for sexual partnership between ethnic groups was reported in Britain [8]. Although we found a relatively higher assortativity among black MSM in general and a non negligible mixing between black ethnic groups from different origins (African, Caribbean and other), HIV transmission seems less assortative 285 among black MSM in the UK than it is in the USA [26].…”
mentioning
confidence: 41%
“…We found that, as has been documented for HIV transmission overall in the United States [21], HIV transmission among MSM was highly assortative by race/ethnicity. Racial/ethnicassortative mixing was especially evident for black/African American MSM.…”
Section: Discussionmentioning
confidence: 63%
“…We used a local version of HIV-TRACE (hivtrace.org), following the protocol outlined by Wertheim et al [18,21] for transmission network construction. Each sequence was aligned to an HIV reference sequence (HXB2, positions 2253 to 2869).…”
Section: Transmission Network Analysismentioning
confidence: 99%
See 1 more Smart Citation